Land use and socio-economic changes in rural Bidayuh community of Bau district - Semuel, Belawan (Universiti Malaysia Sarawak (UNIMAS), 2006)
This study brings forth a local community's perception of land use changes, from the perspective of livelihood options, natural resource and environmental status, land tenure and market place. Since the 1980s rural land use shown dynamic chnages with growing interest in export commodities from rubber to pepper and cocoa and oil palm,and now revisit of rubber following price revival in 2004. With current initiative in modernization of agriculture, more deliberate effort in knowledge transfer is expected of government and agencies to empower rural community to embrace new technology and operational technicalities required in land use programmes ushered in the 9MP plan